(untitled) (Neliniini Kolyvannya, 2025)
We consider the development of qualitative and constructive methods for investigation of linear, weakly perturbed, and weakly nonlinear boundary-value problems for differential, evolutionary and operator equations in the works by O. A. Boichuk and his disciples.